Exploring the Use of Metadiscourse in ESL Coursebooks - Barkhordari Nazarabadi, Alireza ((JELE) Journal Of English Language and Education, 2020)
The pivotal role textbooks play in teaching English as a foreign language (EFL) is undeniable. A great number of studies have focused on English language textbook evaluation by adopting various approaches. Employing Vande Kopple’s (1985) taxonomy of metadiscourse (MD), the present study aimed at building on the existing knowledge of MD through analyzing the writing sections of three EFL coursebooks at intermediate and advanced levels to identify the frequency of MD devices and also whether they put more emphasis on textual or interpersonal MD. Whether the coursebooks presented the discourse markers explicitly or implicitly was also one of the goals of the current study. In-depth analysis of the coursebooks revealed that some categories of MD were more common than others. Textual MD, it was found, enjoyed the highest frequency of use in all the coursebooks. Moreover, coursebooks tended to present discourse markers implicitly, mostly. The findings have implications for teachers, which are discussed at the end.